A responsible fiscal system for Latin America is possible: Dogmatic bases and basic premises constitutive - Rezzoagli, Luciano Carlos (2018)
Effective government action to alleviate social inequalities and boost economic growth, from the strict tax orbit, is a task consciously rejected by theparliament and government. Indeed, they subordinate inclusive public policies, almost exclusively, from "non-commercial" forms, such as those offered by the financial sphere through the use of conditional cash transfers, socialexpenditures and subsidies, tax collection products, others Government revenues and indebtedness. Although in Latin American countries poverty can be temporarily reduce through these government instruments, economic inequality will be maintained or will continue to increase, as will the opportunity grabbing, until there is no structural changes, primarily in the tax field, along with many other integrated solutions beyond the object of our study.